Policy-induced involuntary resettlement: the case of the Mexican Rural Cities Policy. Issue 1 (2nd January 2017) - Mendoza Sammet, Angeles
Abstract: This paper addresses the relocation of Indigenous and rural communities as a result of Mexican government policy called Sustainable Rural Cities which was implemented in the states of Chiapas and Puebla. With the justification that dispersion is a barrier to economic and social development, entire communities were relocated to settlements with pre-defined employment, small houses made of pre-fabricated materials, and no land to continue subsistence agriculture. Once praised by the United Nations, the policy was later criticized for a waste of resources, violations to human and Indigenous rights, and the impoverishment of the relocated communities. With the Mexican government granting numerous mining and oil and gas concessions, reflection on this experience is desirable to improve future involuntary resettlement. The recommendations include: creating clear policy to guide resettlement according to best practice; improving the legal definition of impact; more effective guidelines for the conduct of social impact assessment (the latter introduced in 2014) to specify cultural impacts and human rights; and requiring that social impact assessment be applied to all development projects.